EHEA and education in communication in Spain. The supply structure of postgraduate - Castillo Esparcia, Antonio; Álvarez Nobell, Alejandro; Muñiz Velázquez, José Antonio (Estudios sobre el Mensaje Periodístico, 2013)
Communication has become a backbone of many social, economic and political issues in the current information and knowledge society, leading companies, social organizations, and institutions to make an additional effort on R+D+I. Universities, in the framework of the European Higher Education Area, are ideally placed to lead this process with their research and training policies. In Spain, recent regulatory changes on graduate study levels (RD 99/2011 and RD 1393/2007) have resulted in a new map of university degrees with varying levels of implementation and different features. This text aims to reflect on the supply structure, the training goals (research and/or professional), the geographic distribution, the available places, and other defining features of Spanish postgraduate programs (official Master and Doctoral) in Communication offered by 40 universities (public and private).
Keywords: EHEA; Spain; Communication; Postgraduate; Doctoral; Master.